Akreditasi Sekolah sebagai Suatu Upaya Penjaminan Mutu Pendidikan di Indonesia - Aulia Ar Rakhman Awaludin (SAP (Susunan Artikel Pendidikan), 2017)
This study will discuss the education quality assurance in Indonesia through school accreditation. The methods used in this study are critical analysis and library methods. Quality assurance in education is a systematic and integrated activity performed by an educational unit or program and its practitioners, local and central governments and community in an effort to raise the level of the nation’s intelligence through education. School accreditation, a form of public accountability, is a comprehensive assessment of the feasibility of an educational program with reference to National Education Standards (SNP). Accreditation process is conducted by comparing the real condition of schools to the eight established criteria (standards). In practice, it is the sustainable application and development of these eight standards that lead to the quality education. The implementation of accreditation is expected to encourage or establish an atmosphere conducive to the educational development, to provide directions for conducting sustainable self-evaluation and to be an incentive to continuously achieve the desired quality that can indirectly assure the education quality.